2003
DOI: 10.1191/0269215503cr622oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an ankle-foot orthosis on spatiotemporal parameters and energy cost of hemiparetic gait

Abstract: The orthosis significantly improved self-selected speed (15.47 versus 21.39 m/min), stride cycle (2.33 versus 2.08 s), stance (1.83 versus 1.48 s) and double support (1.55 versus 1.16 s) and reduced energy cost (0.76 versus 0.49 ml O2/kg/m) of walking without affecting cardiorespiratory response. Moreover, a significant correlation was found between the improvement of double support and the reduction of energy cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
82
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 13 publications
4
82
1
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Impairments in ambulation post stroke stem from diminished dorsiflexion of the ankle with resulting sustained plantarflexion and inversion of the ankle during the swing phase of gait, a lack of eccentric control of ankle dorsiflexion during weight acceptance and a decrease in gait velocity. 1,[10][11][12] Multiple studies have demonstrated improved ankle kinematics, improved symmetry, and increased velocity when individuals post stroke walk with an orthosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Impairments in ambulation post stroke stem from diminished dorsiflexion of the ankle with resulting sustained plantarflexion and inversion of the ankle during the swing phase of gait, a lack of eccentric control of ankle dorsiflexion during weight acceptance and a decrease in gait velocity. 1,[10][11][12] Multiple studies have demonstrated improved ankle kinematics, improved symmetry, and increased velocity when individuals post stroke walk with an orthosis.…”
Section: Introductionmentioning
confidence: 99%
“…1,[10][11][12] Multiple studies have demonstrated improved ankle kinematics, improved symmetry, and increased velocity when individuals post stroke walk with an orthosis. [1][2][3][4][5][6][7][8][9] Secondary to the increased understanding of plasticity of the brain, healthcare providers are hesitant to use an AFO for individuals post stroke because they fear using an orthosis encourages disuse of the tibialis anterior (TA) muscle and decreases opportunity for motor relearning with the end result of permanent gait impairments, and a dependence upon bracing. 7,13 Hesse et al 7 investigated electromyography (EMG) of the TA muscle and recorded a decrease in activation when individuals post stroke walked with a rigid AFO compared to walking without an AFO.…”
Section: Introductionmentioning
confidence: 99%
“…20 Previous research has focused primarily on the duration of double support but has failed to further evaluate the specific characteristics of weight transfer during this phase of gait. [30][31][32] As a result, this research focuses on the double support portion of the gait cycle to evaluate transfer of momentum during limb loading using a novel weight transfer analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Foot drop is defined as a weakness or failure of function in the tibialis anterior, causing restricted functional movement, a slowing down of walking speed and an increased risk of falling [1,2]. Several reasons for foot drop have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%